Reconstruction of Sharia Tourism in the New Normal Era Through the Implementation of the Halal Tourism Concept in Indonesia - Izza, Rizqiya Lailatul; Arifin, Adelia Arnanda; Anggarini, Ulifah (Contemporary Issues on Interfaith Law and Society, 2023)
As the global tourism industry navigates through the challenges imposed by the COVID-19 pandemic, the concept of Sharia tourism emerges as a promising avenue for the reconstruction of the tourism sector, particularly in predominantly Muslim countries like Indonesia. This paper explores the potential of implementing the Halal tourism concept as a means to revive and reconstruct Sharia tourism in Indonesia amidst the new normal era. By examining the principles and practices of Halal tourism and analyzing its compatibility with the prevailing socio-cultural and economic landscape of Indonesia, this study aims to offer insights into how Sharia tourism can adapt and thrive in the post-pandemic world. Through a comprehensive review of existing literature, this paper evaluates the feasibility and effectiveness of Halal tourism in Indonesia, considering factors such as infrastructure, policy frameworks, market demand, and stakeholder collaborations. Additionally, it discusses the implications of Halal tourism for economic development, social cohesion, and sustainable tourism practices in Indonesia. The findings of this study contribute to the discourse on the reconstruction of Sharia tourism in the new normal era, providing recommendations for policymakers, industry stakeholders, and community leaders to harness the potential of Halal tourism for inclusive and resilient tourism development in Indonesia.